Indonesian Government Policy Innovation Encouraging Democracy of Media Development - Taufiqurokhman, Taufiqurokhman; Sulastri, Endang; Setiawan, Asep; Dewi, Maya Puspita; Sumarni, Lilik (ANTASENA: Governance and Innovation Journal, 2024)
The research aims to find innovations in the analysis of Indonesian government policies to encourage democratization of media development that is under government control. The analysis of the writing emphasizes the perspective of citizens' rights to media which refers to Article 19, Universal Declaration of Human Rights (UDHR). The research method uses descriptive analysis with qualitative methodology, explaining breakthroughs in policy analysis and the role of government in encouraging media development through primary and secondary data in contributing to the complexity of media issues in empowering civil society through macro and micro level policies. The research population is around 600 media with a sample of around 60 mass media, online media, radio, and television. Research results: there is a rapid liberalization of the media industry, but not all media can survive. Because the sustainability and diversity of the media are determined by economic, political and government regime interests. Research on innovation in government policy roles must be encouraged to follow the development of the rapidly growing digitalization of media platforms compared to the birth of regulations for free and responsible media freedom and educating and educating the nation